Loss of ceramide synthase 5 reduces the development of aortic valve stenosis in mice with high fat diet. (3rd October 2022) - Reese, L; Haenschke, L; Niepmann, S T; Bulic, M; Duesing, P; Zimmer, S; Nickenig, G; Bauer, R; Jansen, F; Zietzer, A
Abstract: Background: Ceramide synthase 5 (CerS5) is essential to maintain C:16 ceramide levels in mice. Ceramides contribute to inflammation and calcification, two hallmarks of aortic valve stenosis development. It is known, that loss of CerS5 function reduces diet-induced obesity. Purpose: The aim of this study was to investigate the effect of ceramide synthase 5 and high-fat diet on the development of aortic valve stenosis with a mouse model. Methods: Our experiment consists of four groups of mice: Wild type (WT) and CerS5 (−/−) mice, with normal and high fat diet. We induced the aortic valve stenosis development through a wire-injury. For this model, a coronary angiography wire is introduced into the left ventricle over the right carotid artery, followed by rotation on the aortic valve level to generate a defined injury. Development of aortic valve stenosis was determined by measuring the peak velocity 14, 28 and 42 days after the wire-injury. With histological analysis of the aortic valve, we measured macrophage infiltration with CD68 immunostaining and calcification using von Kossa staining. For statistical analysis ANOVA and Turkeys multiple comparisons were performed. Results: Histological analysis of the aortic valve revealed, that in CerS5 (−/−) mice with high fat diet (HFD) immune cell infiltration is reduced, while there is no difference between CerS5 (−/−) mice and wild type, when fed with normal diet (A). Also calcification showed a trend towards a reduction in CerS5 mice with high fat diet, but was not statistically significant (B). Echocardiography could detect a reduced peak velocity of CerS5 mice with high fat diet, in comparison to the other groups, four and six weeks after wire injury (C). Conclusion: Our experiments indicate that loss of CerS5 function reduces the development of aortic valve stenosis in mice with high fat diet, by decreasing immune cell infiltration and calcification. Interestingly, in the groups with normal chow, loss of CerS5 function had no effect. In addition, high-fat diet alone had no negative effect in our mouse model. Based on our results it can be assumed that upon high fat diet CerS5 mediates for pro-inflammatory effects in the aortic valve, which are absent on normal diet. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Ernst & Berta Grimmke Foundation (13/19)